Re - appraising the Tax Exemption of Social Enterprises (SEs) in Malaysia: Selected Tax Exemption Theories - Md Radzi, Mohd Shahril Nizam; Mohd Ariffin, Rabiatul Adawiyah; Abd Aziz, Hartinie; Abd Ghadas, Zuhairah Ariff; Anas, Andi Muhammad Aswin (Jambe Law Journal, 2024)
Re-appraising the tax exemption of social enterprises (SEs) in Malaysia from a theoretical perspective involves the underlying frameworks that justify the current tax policies applied to SEs. SEs have increasingly become pivotal in addressing societal challenges such as poverty alleviation, environmental sustainability and community development. The approach taken by Malaysian government to taxing SEs has a notable effect in achieving their social goals. One of the significant constraints for SEs in Malaysia is their tax treatment as business entities. Despite their main purpose is for public good, identical to charitable organizations, SEs are subject to taxation like business entities. Particularly, SEs are not entitled for the tax benefit as offered to charitable organizations. The tax regulatory framework does not recognize a SEs by the legal definition and there are no established tax incentives in the current legal framework that are specific to SEs. Despite the clear fact that charity organizations and charitable activities are exempted from tax, there is no tax exemption granted for SEs in Malaysia. Consequently, SEs are treated as business entities under Income Tax Act 1967. This article utilizes the argument to justify tax exemption for SEs in Malaysia. For the purpose of this discussion, this paper applied library research approach combining legal research methodology which mainly involves document analysis such as case law, legal provision and legal theories to see how they might be used to the subject matter. The paper makes a finding that tax exemption for SEs in Malaysia could be justified based on the theories of Public Good Theory, Donative Theory and the Subsidy Theory. By applying this notion, tax exemption should be granted to SEs not only for charitable organizations